Menganalisis Potensi dan Tantangan Setanga Lestari yang Menjaga Kelestarian Alam dengan Melibatkan Masyarakat - Sasmitha, Dian; Vuspitasari, Benedhikta Kikky (ECONOMETRICS:Journal of Sustainable Economics and Management, 2025)
The development of tourist attractions is one of the common problems that will be faced by the local community, especially in Sebente village, when an area has a tourist attraction, because if the development is managed properly, the tourist attractions that are studied are established as tourist attractions and are expected to be able to maintain the preservation of environmental objects that are still beautiful. The purpose of this research is to find out and get benefits from the development of tourist attractions into tourist villages that can expand business opportunities by improving tourist facilities by implementing the cleanliness of tourist attractions by involving local communities so that interaction between tourists is established, this research uses a qualitative method. Sampling techniques are in the form of purposive sampling, data collection techniques using observation, interviews and documentation. Data analysis is carried out qualitatively with the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that the development of tourist villages can be seen from the increasing number of tourist visits in Setanga Lestari and the characteristics of tourist villages that are the attraction of tourist attraction development. The participation of the surrounding community can be seen from the support of the community who participated in the development of the tourist village. With the existence of this tourist village, it can open up business opportunities and increase the income of the people in the area